Binder for molding mold and composition for molding mold

By dissolving aluminum silicate in water glass to form a water glass adhesive containing 2 to 15 parts by mass of aluminum silicate, the problem of precipitation of adhesive in storage in the prior art is solved, and bonding for casting molding is realized Long-term storage stability and heat resistance of the agent.

CN119489159APending Publication Date: 2025-02-21SINTOKOGIO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411090362.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-14
Filing Date
2024-08-09
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing water glass adhesive for casting mold molding inevitably produces additive precipitation during storage, resulting in insufficient long-term storage stability.

Method used

By dissolving aluminum silicate in the water glass, a water glass adhesive containing 2 to 15 parts by mass of aluminum silicate is formed, thereby improving the heat resistance and stability of the adhesive.

Benefits of technology

It achieves excellent long-term storage stability of the adhesive for casting mold molding, avoids the precipitation of additives, and ensures the dimensional accuracy and quality of the casting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119489159A_ABST
    Figure CN119489159A_ABST
Patent Text Reader

Abstract

A binder for molding a mold, which contains water glass and aluminum silicate that is formed by dissolving in the water glass, and which contains 2-15 parts by mass of the aluminum silicate per 100 parts by mass of the solid content of the water glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a binder for casting molds and a composition for casting molds. Background Art

[0002] As a binder for casting, a water glass binder is known that generates little odor during molding or pouring. As such a water glass binder, a water glass binder comprising a water glass solution and a natural and / or synthetic additive having a particle size of less than 5 μm has been studied (for example, see Patent Document 1).

[0003] Patent Document 1: Japanese Patent Application No. 2016-533275

[0004] In the prior art, attempts have been made to suppress the precipitation of additives in adhesives by using particulate additives. However, since the additives are merely dispersed in the adhesive, precipitation of the additives is unavoidable during storage. Summary of the invention

[0005] The present disclosure has been made in view of the above circumstances, and an object of the present invention is to provide a mold-forming binder having excellent long-term storage stability.

[0006] Another object of the present disclosure is to provide a casting mold composition comprising the casting mold binder.

[0007] A binder for casting molds according to one aspect of the present disclosure includes water glass and aluminum silicate dissolved in the water glass, and includes 2 to 15 parts by mass of the aluminum silicate based on 100 parts by mass of the solid content of the water glass.

[0008] According to the present disclosure, a mold-forming adhesive having excellent long-term storage stability is provided.

[0009] Furthermore, according to the present disclosure, there is provided a casting mold composition comprising the casting mold binder. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 A is a cross-sectional view showing the dimensional structure of the mold.

[0011] Figure 1 B is a cross-sectional view showing the dimensional structure of the mold.

[0012] Figure 1 C is a cross-sectional view showing the deformation amount of the casting.

[0013] Figure 2 This is a graph showing the relationship between the presence or absence of addition of aluminum silicate to the glass binder and the amount of deformation of the through hole. DETAILED DESCRIPTION

[0014] <Overview of Embodiments of the Invention>

[0015] The embodiments of the present disclosure include the following aspects, for example.

[0016] [1] A binder for casting molds, comprising water glass and aluminum silicate dissolved in the water glass, wherein the binder comprises 2 to 15 parts by mass of the aluminum silicate per 100 parts by mass of the solid content of the water glass.

[0017] [2] The binder for casting according to [1], comprising 40 to 55% by mass of a solid content of the water glass and the aluminum silicate.

[0018] [3] The binder for casting molds according to [1] or [2], wherein the aluminum silicate is synthetic aluminum silicate.

[0019] [4] A casting mold making composition comprising refractory inorganic particles and the casting mold making binder according to any one of [1] to [3].

[0020] Hereinafter, preferred embodiments of the present disclosure will be described in detail, but the present disclosure is not limited to the following embodiments.

[0021] <Adhesive for casting molds>

[0022] The binder for casting molds contains water glass and aluminum silicate dissolved in water glass. Hereinafter, the binder for casting molds may be simply referred to as a binder.

[0023] Water glass is an aqueous solution in which alkali metal silicates are dissolved. Alkali metal silicates are, for example, compounds represented by the general formula xSiO2·yM2O·zH2O (M is an alkali metal such as Na, K, Li, etc.). Among them, sodium silicates such as Na2SiO3, Na4SiO4, Na2Si2O5, and Na2Si4O9 can be preferably used as alkali metal silicates from the viewpoint of high marketability and low cost. These sodium silicates can be divided into types 1 to 5 according to the molar ratio of SiO2 / Na2O as described below. However, in addition to the following sodium silicates No. 1 to No. 5, sodium metasilicate having a molar ratio of SiO2 / Na2O of 1.0 can also be used. These (methyl) sodium silicates are already on sale and can be easily obtained.

[0024] No. 1: The molar ratio of SiO2 / Na2O is 2.0 to 2.3.

[0025] No. 2: The molar ratio of SiO2 / Na2O is 2.4 to 2.5.

[0026] No. 3: The molar ratio of SiO2 / Na2O is 3.1 to 3.3.

[0027] No. 4: The molar ratio of SiO2 / Na2O is 3.3 to 3.5.

[0028] No. 5: The molar ratio of SiO2 / Na2O is 3.6 to 3.8.

[0029] By mixing these sodium silicates, the molar ratio of SiO2 / Na2O can be adjusted.

[0030] If the molar ratio of SiO2 / Na2O becomes smaller, the amount of free alkali hydroxide increases, but from the viewpoint of the solubility of aluminum silicate, the molar ratio is preferably 3.3 or less, more preferably 3.0 or less, and further preferably 2.5 or less. That is, in the above classification of sodium silicate, sodium silicate with a small number can be more appropriately used.

[0031] The solid content of water glass refers to the non-volatile components (water glass components) obtained by removing water from water glass, and specifically, corresponds to water-soluble alkaline silicates such as sodium silicate. The amount of solid content in water glass is adjusted according to the molar ratio of water glass, but in order to facilitate the handling such as the supply method of the binder during mold formation, water can be added to adjust the viscosity.

[0032] The aluminum silicate used here is a compound represented by the general formula Al2(SiO3)3·nH2O(n; 2-3) (manufactured by Kishida Chemical Co., Ltd.) or Al2(SiO3)3 (manufactured by FUJIFILM Corporation), which is a so-called synthetic aluminum silicate. By using synthetic aluminum silicate as aluminum silicate, not only a one-component binder can be obtained, but also excellent heat resistance is also obtained, so deformation of the mold can be suppressed.

[0033] From the viewpoint of improving the heat resistance of the adhesive, the amount of aluminum silicate in the adhesive is 2 parts by mass or more, preferably 4 parts by mass or more, based on 100 parts by mass of the solid content of water glass.

[0034] On the other hand, from the viewpoint of the solubility of aluminum silicate, the handling properties of the adhesive, etc., the amount of aluminum silicate is 15 parts by mass or less, and preferably 10 parts by mass or less.

[0035] From the viewpoint of moldability and the like, the solid content of water glass and aluminum silicate in the binder is preferably 40% by mass or more, more preferably 43% by mass or more.

[0036] On the other hand, from the viewpoint of kneadability with aggregates, the amount is preferably 55% by mass or less, more preferably 50% by mass or less.

[0037] The binder can be prepared by dissolving aluminum silicate in water glass. The method for preparing the binder is not particularly limited as long as the aluminum silicate can be dissolved in water glass, and an example thereof is a method of dissolving the aluminum silicate while heating the water glass. In this case, from the viewpoint of improving the solubility of the aluminum silicate, it is preferred to use particles as fine as possible as the aluminum silicate.

[0038] <Molding Composition>

[0039] The composition for casting molds may include the above-mentioned casting mold binder and refractory inorganic particles and a curing agent or a heat-generating agent. The curing agent is used to act with the binder to perform casting molds, and a representative example is propylene carbonate. The heat-generating agent generates heat by reacting with water glass, and a representative example is ferrosilicon.

[0040] The mold-making composition may not contain these agents, but may be molded by neutralizing and gelling the binder using an acidic gas such as carbon dioxide (core molding method 2 described later).

[0041] (Refractory Inorganic Particles)

[0042] As refractory inorganic particles (refractory aggregates), natural sands with inorganic oxides such as silicon oxide and aluminum oxide as the main component or artificial sands with them as the main component can be cited. The particle size of the refractory inorganic particles is preferably 30 to 120 in the AFS particle size index, and more preferably 50 to 100. In castings where the surface of the casting is important, the refractory inorganic particles preferably have a certain degree of fineness. On the other hand, in order to prevent gas defects in the casting, the refractory inorganic particles preferably have a certain degree of roughness in order to ensure the air permeability of the mold.

[0043] The amount of the binder in the composition for casting mold molding is preferably 0.1 to 10 parts by mass, more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the refractory inorganic particles. The binder affects the strength of the mold. The amount of the binder can be appropriately adjusted according to the particle size and particle shape of the refractory inorganic particles used. When it is desired to obtain sufficient mold strength (for example, more than 1 MPa), when fine refractory inorganic particles are used, the surface area of ​​the particles becomes larger, so it is preferred to increase the amount of the binder to a certain extent. In addition, when coarse refractory inorganic particles and refractory inorganic particles with high sphericity are used, the surface area of ​​the particles becomes smaller, so the amount of the binder can be reduced to a certain extent.

[0044] (Curing agent)

[0045] The mold-forming composition may contain a curing agent for accelerating the curing of the mold-forming composition. As the curing agent, a curing agent represented by propylene carbonate that forms an ester bond with water glass can be used. The curing agent is used in the core molding method 1 described later.

[0046] The amount of the curing agent in the casting mold making composition is preferably 0.05 to 5.0 parts by mass, more preferably 0.1 to 1.0 parts by mass, based on 100 parts by mass of the refractory inorganic particles.

[0047] (Heat accelerator)

[0048] The composition for casting molds may contain a heat-generating accelerator represented by metal silicon or ferrosilicon. The heat-generating accelerator may be used in the core molding method 3 described later.

[0049] The amount of the heat-generating accelerator in the casting mold forming composition is preferably 0.5 to 5.0 parts by mass, more preferably 1.0 to 3.0 parts by mass, based on 100 parts by mass of the refractory inorganic particles.

[0050] The casting mold making composition can be obtained by mixing the casting mold making binder, the refractory inorganic particles, and other components such as a curing agent as required, using a mixer or the like.

[0051] Example

[0052] The present disclosure will be described in further detail by the following examples, but the present disclosure is not limited to these examples.

[0053] <Preparation of Binder (Binder for Casting Molds)>

[0054] A predetermined amount of No. 1 water glass (manufactured by Fuji Chemical Co., Ltd., solid content 48% by mass) and synthetic aluminum silicate powder (manufactured by Kishida Chemical Co., Ltd.) were placed in a 1L glass beaker. The glass beaker was then placed on a hot plate at 80°C and stirred with a table stirrer to dissolve the aluminum silicate powder. Thus, the water glass adhesive of the present invention containing aluminum silicate dissolved in No. 1 water glass was prepared.

[0055] The water glass binder contained 5.2 parts by mass of aluminum silicate based on 100 parts by mass of the solid content (alkaline silicate) of No. 1 water glass, and contained a total of 49.3% by mass of the solid content of No. 1 water glass and aluminum silicate.

[0056] In visual observation immediately after preparation, the water glass binder was transparent, and no aluminum silicate powder dispersed in the binder was confirmed.

[0057] The water glass adhesive of the present invention remained transparent even after being left to stand in a room at about 25° C. for 200 days, and no precipitation of aluminum silicate was observed.

[0058] On the other hand, a water glass adhesive was prepared in the same manner as above using No. 1 water glass (manufactured by Fuji Chemical Co., Ltd.) and white powder of anhydrous aluminum silicate (SP33 manufactured by BASF, synthetic aluminum silicate powder). As a result, a transparent water glass adhesive was not obtained. Aluminum silicate powder was confirmed to be dispersed in the adhesive. In addition, after standing still in a room at 25° C. for 200 days, precipitation of aluminum silicate was confirmed.

[0059] This shows that the water glass adhesive of the present invention is excellent in long-term storage stability.

[0060] <Core shape>

[0061] Next, a core molding composition was prepared using the water glass adhesive of the present invention prepared as described above, and core molding was performed. When molding the core, the water glass adhesive of the present invention was left to stand for more than 30 days in a room at 25° C. before use. In addition, the following three types of refractory aggregates (sand) were prepared.

[0062] ·ESPEARL 60L (manufactured by Yamakawa Industry Co., Ltd.)

[0063] ·NAIGAI CERABEADS 650 (manufactured by ITOCHU CERATECH CORP)

[0064] ·Mikawa R No. 5.5 (manufactured by Mikawa Silica Co., Ltd.)

[0065] (Core molding method 1: Curing agent curing mold molding)

[0066] A certain amount of refractory aggregate was put into a mixer (KENMIX, manufactured by Aikosha Co., Ltd.), and then a predetermined amount (0.5 parts by mass relative to 100 parts by mass of aggregate) of propylene carbonate liquid (Azuchi Sangyo Co., Ltd.) was added and kneaded for 1 minute. A predetermined amount (3.0 parts by mass relative to 100 parts by mass of aggregate) of the water glass binder of the present invention was added thereto and further kneaded for 1 minute. Then, the kneaded product (composition for core molding) was taken out from the mixer, filled into a mold for core molding (core size: 15 mm×20 mm×159 mm, 5 pieces were taken), compacted, and demolded after standing for 24 hours to obtain a core 1.

[0067] On the other hand, a core 1C was obtained in the same manner as above except that No. 1 water glass was used instead of the water glass binder of the present invention.

[0068] (Core molding method 2: Carbon dioxide curing mold molding)

[0069] A certain amount of refractory aggregate is put into a mixer, and then a specified amount (3.0 parts by mass relative to 100 parts by mass of aggregate) of the water glass adhesive of the present invention is put into the mixer, and kneaded for 1 minute. Then, the kneaded product is taken out from the mixer, filled into a core molding mold, and compacted. Then, carbon dioxide is pressed into the mold in about 3 minutes through the pipe of a carbon dioxide gas cylinder, and demoulding is performed after standing for 24 hours to obtain a core 2.

[0070] On the other hand, a core 2C was obtained in the same manner as above except that No. 1 water glass was used instead of the water glass binder of the present invention.

[0071] (Core molding method 3: heat curing mold molding)

[0072] A certain amount of refractory aggregate was put into a mixer, followed by a predetermined amount (3.0 parts by mass relative to 100 parts by mass of aggregate) of silica powder (manufactured by Kanto Metal Co., Ltd.), and kneading for 1 minute. A predetermined amount (3.0 parts by mass relative to 100 parts by mass of aggregate) of the water glass binder of the present invention was put into the mixer, and kneading was further performed for 1 minute. Then, the kneaded product was taken out of the mixer, filled into a mold for core molding, compacted, and demolded after standing for 24 hours to obtain a core 3.

[0073] On the other hand, a core 3C was obtained in the same manner as above except that No. 1 water glass was used instead of the water glass binder of the present invention.

[0074] <Casting Test>

[0075] Next, a casting test was performed using the cores 1 to 3 or the cores 1C to 3C obtained by the core molding methods 1 to 3 described above.

[0076] Figure 1 A is a cross-sectional view showing the dimensional structure of the mold M. Figure 1 A is a cross-sectional view of the mold M as viewed from the Y direction. The Y direction is along the short side direction of the mold M.

[0077] Figure 1 B is a cross-sectional view showing the dimensional structure of the mold M. Figure 1 B is a cross-sectional view of the mold M as viewed from the X direction orthogonal to the Y direction. The X direction is along the longitudinal direction of the mold M.

[0078] Figure 1 C is a cross-sectional view showing the amount of deformation of the casting C. Figure 1 C is a cross-sectional view of the casting C viewed from the Y direction.

[0079] like Figure 1 A and Figure 1 As shown in B, the casting mold M includes an upper mold, a lower mold and a core MC.

[0080] Figure 1 The casting C shown in C is formed by pouring gray cast iron (FC 250) into a casting mold M. The temperature of the molten metal during the pouring is 1400°C.

[0081] like Figure 1 As shown in FIG. 3 , the casting C is in the shape of a rectangular parallelepiped. A through hole H is formed in the casting C, which passes through the casting C along the X direction. The through hole H is a portion formed by the core MC. The length of the casting C in the X direction is 140 mm, the length in the Z direction is 35 mm, and the length in the Y direction is 40 mm. The length of the through hole H in the Z direction is 15 mm, and the length in the Y direction is 20 mm.

[0082] like Figure 1 As shown, the deformation amount d of the through hole H in the Z direction was measured for each of the cores 1 to 3 or cores 1C to 3C used. The deformation amount d is the maximum width between the end of the opening of the through hole H in the Z direction and the end of the center of the through hole H in the Z direction. The deformation amount d is equivalent to the deformation amount of the core MC of the casting C in the Z direction.

[0083] Figure 2 : is a coordinate diagram showing the relationship between the addition of aluminum silicate to the glass binder and the amount of deformation of the through hole. In the example of using ESPEARL 60L as the core 1, the amount of deformation d is 0 mm (not shown). Figure 2 As shown, it can be seen that the water glass adhesive of the present disclosure can significantly suppress the deformation of the through hole compared to the case of using No. 1 water glass. The water glass adhesive of the present disclosure has excellent heat resistance, and thus can produce a casting with high dimensional accuracy.

Claims

1. A binder for casting molds, comprising water glass and aluminum silicate dissolved in the water glass, wherein the aluminum silicate is contained in an amount of 2 to 15 parts by mass based on 100 parts by mass of a solid content of the water glass.

2. The binder for casting molds according to claim 1, wherein The casting mold binder contains 40 to 55% by mass of the solid content of the water glass and the aluminum silicate.

3. The binder for casting molds according to claim 1, wherein The aluminum silicate is synthetic aluminum silicate. 4 . A casting mold making composition comprising refractory inorganic particles and the casting mold making binder according to claim 1 .

Citation Information

Patent Citations

  • Method for producing lost cores or moldings for casting production

    JP2016533275A